Application of central composite design for preparation of kenaf fiber based activated carbon for adsorption of manganese (II) ion - Chowdhury, Z.Z.; Arami-Niya, A.; Ahmad, A.A.; Islam, M.S.; Khan, R.A.; Zain, Sharifuddin Md (2011)
The objective of this research is to define optimum operating conditions for preparation of activated carbon from kenaf fiber which would conciliate for highest removal efficiency of manganese (II) ions along with maximum possible yield. Kenaf fiber (KF) is used to prepare activated carbon by using two step; physiochemical activation method which consisted of potassium hydroxide treatment (KOH) with carbon dioxide gasification. The effects of three preparation variables; temperature (500 to 700°C), time (1 to 3 h) and KOH impregnation ratio, IR (1-3) on the percentage yield and removal percentage of Mn (II) ions were investigated. Based on central composite design (CCD), quadratic models were developed to correlate activated carbon preparation variables with the aforementioned two responses. From the analysis of variance (ANOVA), the most influential factor on each experimental design response was identified. The optimum conditions determined were: activation temperature, activation time and impregnation ratio, IR of 574°C, 1.31 h and 3, respectively. The application of prepared activated carbon under optimum condition was further analyzed by Langmuir, Freundlich and Temkin isotherm. The values of Langmuir separation factor, R L and Freundlich exponent, 1/n were less than 1 reflecting favorable process for adsorption. © 2011 Academic Journals.